Japanese quail (Coturnix coturnix japonica) as newcastle disease virus carrier - Lima, Fabiana Silva [UNESP]; Santin, Elizabeth; Paulillo, Antonio Carlos [UNESP]; Doretto, Luciano; de Moraes, Vera Maria Barbosa [UNESP]; Schocken-Iturrino, Ruben Pablo [UNESP] (My University, 2004)
This study was carried out to clarify the real role that was played by the quail (Coturnix coturnix japonica) in the epidemiological plan, under the perspective as infection source of the Newcastle disease virus (NDV). For this, they used specific-pathogen-free birds (SPF) that were housed with inoculated quails with a pathogenic strain (velogenic viscerotropic), of NDV (DIE50=108,15/0.1 ml), by the ocular-nasal via. Each group was composed by 6 SPF birds and 12 Japanese quails. After 4, 14 and 20 days since the inoculation of the quails with NDV, 6 SPF birds were put together with each group of quails, so that there was a direct contact among the species. After 5, 14 and 20 days since the challenge of the quails with NDV, the samples were collected through the vent swabs of the quails for the viral isolation (pathogenic virus) in SPF embryos. There was no clinical disease in the quails inoculated with NDV. Therefore, there was viral isolation from 5 to 14 days after the challenge with the NDV, demonstrating, this way the state of carrier of the quail NDV, which happened until 14 days of the experimental infection with this pathogen. So, 100% of the SPF birds which housed with the NDV infected quail, after 5 (group 1) and 14 days (group 2), died from 4 to 7 days after the direct contact among species. This way, the transmission of the pathogenic virus of the quail was evident until 14 days of the experimental infection with this pathogen (NDV) for the SPF birds that housed together, and that calls the attention to the importance of the quail from the epidemiological point of view as potential source of infection of the NDV to commercial birds that housed with these specie or near this breeding. © Asian Network for Scientific Information, 2004.
Keywords: Epidemiology; Japanese quail; NDV carrier; Newcastle disease